Activity and Selectivity of Mesoporous Silica Catalyst for Hydrocracking Process of Used Palm Oil into Biogasoline - Ahmad Suseno; Karna Wijaya; Edy Heraldy; Lukman Hakim; Wahyu Dita Saputri; Gunawan Gunawan (Indonesian Journal of Chemistry, 2023)
Research on the synthesis of mesoporous silica catalyst, as well as its activity and selectivity in the hydrocracking of used palm oil, has been carried out. The research involved the preparation of mesoporous silica catalyst by varying the volume ratio of TEOS:CTAB at 2:1, 4:1, and 8:1, then calcined at 500 °C. Synthesis success was confirmed by FTIR, XRD, SEM-EDX, GSA, and hydrocracking selectivity by GC-MS analysis. The results showed that the more TEOS added, the silica bond composition, crystallinity, pore size, and product selectivity increased. The best catalyst performance was obtained from a TEOS:CTAB ratio of 8:1 at a calcination temperature of 500 °C (MCT81-500), which indicated the presence of Si-OH and Si-O-Si groups with a Si percentage of 45.31%, pore size diameter of 31.912 nm, and a total pore volume of 0.040 cc/g. In addition, the application of MCT81-500 in the hydrocracking process of used palm oil can produce a bio-gasoline (C5-C12) and kerosene (C12-C15) of 92.24 and 7.76 wt.%, respectively. This study shows that mesoporous silica has good potential for catalytic activity to convert used cooking oil waste into an environmentally friendly energy source.